Peran Pendidikan Dalam Membuat Refleksi Politik Dan Etika Peserta Didik SMPN 1 Parengan - Joy Ardha Abdurroziqin; Sri Minarti (CV. ITTC INDONESIA, 2026)
Education has an essential role in shaping students’ political awareness and ethical attitudes in school life. This study aims to analyze the role of education in building political reflection and ethical behavior among students at SMPN 1 Parengan. The research employed a qualitative descriptive approach through observation, interviews, and documentation. The findings indicate that political and ethical reflection among students can be developed through classroom learning, school regulations, organizational activities, and teachers’ role modeling. Civic Education subjects and character education programs contribute significantly to strengthening students’ understanding of responsibility, tolerance, discipline, and democratic values. In addition, the school environment supports students in expressing opinions respectfully and participating actively in social activities. Therefore, education does not merely function as a process of knowledge transfer but also as a medium for cultivating ethical awareness and political responsibility among students.